Knowing What Truth Is: Some Brief Remarks on the Erotetic Account - GUILHERME CARDOSO (Manuscrito)
Abstract This submission is addressed to the symposium on Prof. André Abath’s book “Knowing What Things Are: An Erotetic-Based Account” (2022).